Soil mapping, fertilizer application, and maize yield: A spatial econometric approach - Ulimwengu, John M.; Kibonge, Aziza (AKADEMIYA2063, 2022)
Despite the increasing availability of precision agriculture technology, most farmers in developing countries are still practicing farming with limited reliable information on soil characteristics. Using a unique geo-referenced dataset from the Democratic Republic of Congo, this article provides empirical insights on the spatial effects of fertilizer application on maize yield while estimating the size and direction of spatial spillover effects (direct and indirect effects) from leaching and runoff. Three fertilizer application scenarios are examined: i) homogeneous fertilizer application, ii) site-specific or heterogeneous, and iii) site-specific with spillover effects. Maize yield response is then assessed for the three scenarios. We found significantly higher maize yields under site-specific application (8.4 tons/ha) compared to homogeneous application (2.0 ons/ ha). Our findings also provide evidence of spillover effects as the average maize yield is reduced by 1.9 tons/ha when spatial spillovers are accounted for. As anticipated, farmers’ profitability with homogeneous fertilizer application is lower in comparison to site-specific application. Furthermore, excluding areas with potentially lower gross profit margins results in a 35.6 percent increase in gross profit (site-specific), and a 22.7 percent increase (site-specific with spillovers).